REORIENTASI DAN REKONSTRUKSI PEMIKIRAN PENDIDIKAN AGAMA ISLAM DI ERA DISRUPSI DI SDN 053 CISITU KOTA BANDUNG - Iyad Suryadi; Diki sulaiman; Abdul latip (STKIP Subang, 2026)
This study examines the reorientation and reconstruction of Islamic Religious Education (IRE/PAI) thought in the era of technological disruption, with a research locus at SDN 053 Cisitu, Bandung City. The disruption era has brought fundamental changes to the educational landscape, demanding a paradigmatic transformation in the approaches, methods, and learning media of PAI, which has long been dominated by conventional lecture-based methods. This study employs a descriptive qualitative method with a case study approach following Lexy J. Moleong. Data were collected through document analysis of Grade VI PAI lesson plans (RPP), classroom observations, and in-depth interviews with teachers and students. Data analysis techniques encompassed data reduction, data presentation, and data verification. The findings reveal that the reorientation of PAI at SDN 053 Cisitu is characterized by the reinforcement of digital literacy, the application of Problem Based Learning (PBL), interactive discussions, and the integration of moral values including humility, discipline, and responsibility. The reconstruction of PAI thought is manifested through a shift from traditional lecture methods to the use of interactive multimedia such as PowerPoint, YouTube videos, Google Meet, and WhatsApp Group, as well as the contextualization of subject matter through empirical examples such as natural disasters as illustrations of the minor apocalypse (kiamat sugra) and faith reinforcement through case-based reflection. The study concludes that the adaptive reconstruction and reorientation of PAI in the disruption era can enhance the relevance, meaningfulness, and effectiveness of PAI learning at the elementary school level.